A comparison of apical microleakage after lateral condensation of different tapered master cone in canals prepared by ProFile rotary instruments (Mustansiria Dental Journal, 2018)
Forty five mesial canals of extracted human mandibular molars were instrumentedwith ProFile ISO .06 nickel-titanium rotary instruments and obturated with lateralcondensation using three different master cones: .06 tapered gutta-percha cone (groupI), .04 tapered gutta-percha cone (group II), .02 tapered gutta-percha cone (group III).Zinc oxide eugenol sealer was used in all groups. After 48 hours in an incubator, theroots were coated with nail polish and were the submerged in methylene blue dye for72 hours. The roots were then split longitudinally and the apical leakage measuredand compared for each group. Although there was no statistical significant differenceamong groups (P>0.05), group (I) with .06 tapered gutta-percha master cone showedthe lowest mean of dye penetration.